Hippocampal synaptic pathology in schizophrenia, bipolar disorder and major depression: a study of complexin mRNAs. - Eastwood, S; Harrison, P (2000)
Complexin (cx) I and cx II are synaptic proteins preferentially expressed by inhibitory and excitatory hippocampal neurons respectively. We previously reported decreased hippocampal formation cx mRNA and protein expression in schizophrenia, with a greater loss of cx II than cx I. The present in situ hybridization study was both an attempt at replication, and an extension to include bipolar and unipolar mood disorders, using sections from the Stanley Foundation brain series. In schizophrenia, both mRNAs were decreased in some hippocampal subfields, especially CA4, but were preserved in subiculum. The cx II/cx I mRNA ratio was unchanged. In bipolar disorder, the mRNAs were reduced in CA4, subiculum and parahippocampal gyrus, with the deficit in subiculum being diagnostically specific. No alterations in cx mRNAs were found in major depression. Treatment of rats with antipsychotics (haloperidol or chlorpromazine) for 2 weeks had no effect on hippocampal cx mRNAs. These data replicate the finding of decreased cx I and cx II expression in the hippocampus in schizophrenia and show a similar or greater abnormality in bipolar disorder. Non-replication of the cx II > cx I mRNA loss in schizophrenia means that the hypothesis of a preferential involvement of excitatory connections was not supported. The results extend the emerging evidence that altered circuitry may be a component of the neuroanatomy of both schizophrenia and bipolar mood disorder.